Muslim struggles for shariah courts in Thailand: an analytical study - Wan Muhammad, Ramizah (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2014)
Muslims, especially in southern Thailand, have been struggling to lead their lives according to Shari’ah. They have been demanding independence or at least autonomy especially for the southern part of Thailand from the central government. Their aim is to transform the socio-economic and political set-up in the South along Islamic lines. They began with the demand for Shariah Courts to be established in the region. This struggle for Shari’ah court is in accordance with the fundamental right enshrined in the Universal Declaration of Human Rights that stipulates that every person has the right to practice his/her religion. This is also required by religion. Muslims are under obligation to live according to the Islamic way of life and to settle disputes among fellow Muslims through Shari’ah courts. However, Muslims are denied the right to Shari’ah court. There are no procedural laws and adequate substantive laws to govern their practical lives. The mass media highlights the insurgency that is taking place in southern Thailand but not the inequality and injustices Muslims face in the region. Muslims have been marginalized in almost every aspect despite being the citizens of the kingdom. This paper analyses the current situation regarding the status of Shari’ah courts in Thailand, analyses albeit briefly the injustices meted out to the Muslims and argues for granting the right to Shari’ah court in Thailand.